Ejector-based sampling from low-pressure aerosol reactors. (September 2018) - Rosenberger, Thore; Münzer, Adrian; Kiesler, Dennis; Wiggers, Hartmut; Kruis, Frank Einar
Abstract: Online measurements of nanoparticles are necessary when rapid information about the particle size and mass distribution is needed. Currently, the application of online measurement techniques with commonly used instruments such as SMPS, CPMA and ELPI+ is not possible at low-pressure conditions. In this work, a commercial vacuum ejector is used as a simple tool to transfer nanoparticles from a low-pressure region to atmospheric pressure. The vacuum ejector is investigated for different process pressures between 120 and 170 mbar to measure size-selected aerosols in the range from 10 to 100 nm. It was found that the sampling with the vacuum ejector does not change the particle size. The gas and particle dilution factors as well as the particle losses are determined, so that quantitative measurements of the aerosol size distribution can be obtained. Additionally, the applicability of the vacuum ejector is tested during particle synthesis in a low-pressure microwave plasma reactor with a combination of online instrumentation. The direct transfer of the aerosol to atmospheric pressure allows real-time measurements. The primary particle size, mass mobility exponent and effective density are calculated exemplary based on parallel online ELPI+, SMPS and CPMA measurements and are compared to offline TEM analysis. Highlights: Vacuum ejector as a low-cost method to sample aerosol from low pressure environments. Sampling from 100–170 mbar inlet pressure and transfer to atmospheric pressure. Determination of the ejector's transfer characteristic for quantitative measurements. Demonstration of real-time measurement applicability at a low pressure reactor with atmospheric online instrumentation.